Utilization of tall oil to enhance natural fibers for composite applications and production of a bioplastic. Issue 48 (19th August 2016) - George, Michael; Mussone, Paolo G.; Bressler, David C.
ABSTRACT: Tall oil is one of the side products from the kraft pulping process of lignocellulosic material. The most abundant acid found in this crude viscous material is abietic acid. Strangely, in the past, the utilization of tall oil has been limited to incineration for cogeneration of power. In this study, tall oil rosin acids (TORAs) were used in two different applications. First, it was used to enhance the hydrophobicity and thermal properties of hemp fibers. Second, TORAs were used to supplement epoxy for the production of a polymeric material. The reaction conditions from a model study were mimicked using a crude tall oil rosin acid mixture to enhance hemp fibers. Treated hemp fibers were characterized with increased surface hydrophobicity and improved thermal properties. Also, IR and X‐ray photoelectron spectroscopy confirmed successful chemical modification and grafting of carbon rich moieties onto the surface of the fibers, respectively. Furthermore, TORAs were used to supplement epoxy resin and produced plastics with comparable properties to pure epoxy based plastics. Specifically, 25% (w/w) replacement exhibited little difference in thermal stability and curing when compared to virgin epoxy plastics. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44327. Abstract :